Association of single and joint metals with albuminuria and estimated glomerular filtration longitudinal change in middle-aged adults from Spain: The Aragon workers health study. (1st February 2023) - Grau-Perez, Maria; Domingo-Relloso, Arce; Garcia-Barrera, Tamara; Gomez-Ariza, Jose L.; Leon-Latre, Montserrat; Casasnovas, J. Antonio; Moreno-Franco, Belen; Laclaustra, Martin; Guallar, Eliseo; Navas-Acien, Ana; Pastor-Barriuso, Roberto; Redon, Josep; et al.
Abstract: The nephrotoxicity of low-chronic metal exposures is unclear, especially considering several metals simultaneously. We assessed the individual and joint association of metals with longitudinal change in renal endpoints in Aragon Workers Health Study participants with available measures of essential (cobalt [Co], copper [Cu], molybdenum [Mo] and zinc [Zn]) and non-essential (As, barium [Ba], Cd, chromium [Cr], antimony [Sb], titanium [Ti], uranium [U], vanadium [V] and tungsten [W]) urine metals and albumin-to-creatinine ratio (ACR) (N = 707) and estimated glomerular filtration rate (eGFR) (N = 1493) change. Median levels were 0.24, 7.0, 18.6, 295, 3.1, 1.9, 0.28, 1.16, 9.7, 0.66, 0.22 μg/g for Co, Cu, Mo, Zn, As, Ba, Cd, Cr, Sb, Ti, V and W, respectively, and 52.5 and 27.2 ng/g for Sb and U, respectively. In single metal analysis, higher As, Cr and W concentrations were associated with increasing ACR annual change. Higher Zn, As and Cr concentrations were associated with decreasing eGFR annual change. The shape of the longitudinal dose-responses, however, was compatible with a nephrotoxic role for all metals, both in ACR and eGFR models. In joint metal analysis, both higher mixtures of Cu–Zn–As–Ba–Ti–U–V–W and Co–Cd–Cr–Sb–V–W showed associations with increasing ACR and decreasing eGFR annual change. As and Cr were main drivers of the ACR change joint metal association. For the eGFR change joint metal association, while Zn and Cr were main drivers, other metals also contributed substantially. We identified potential interactions for As, Zn and W by other metals with ACR change, but not with eGFR change. Our findings support that Zn, As, Cr and W and suggestively other metals, are nephrotoxic at relatively low exposure levels. Metal exposure reduction and mitigation interventions may improve prevention and decrease the burden of renal disease in the population. Graphical abstract: Image 1 Highlights: High Zn, As, Cr, and W were associated with adverse longitudinal renal endpoints. Joint metal associations were mainly driven by As and Cr for ACR, and Zn and Cr for eGFR. As, Zn, and W showed interactions by other metals with ACR, but not eGFR. Metal exposure reduction and mitigation may decrease the renal disease burden.